TiO2 surface functionalization of COC based planar waveguide Bragg gratings for refractive index sensing - Rosenberger, Manuel; Girschikofsky, M.; Förthner, Michael; Belle, S.; Rommel, Mathias; Frey, Lothar; Schmauß, Bernhard; Hellmann, R. (Journal of Optics, 2018)
We demonstrate the applicability of a planar waveguide Bragg grating in cyclo-olefin copolymer (COC) for refractive index sensing. The polymer planar waveguide Bragg grating fabricated using a single writing step technique is coated with a high-index layer of titanium dioxide (TiO2) leading to a distinct birefringence. This in turn results in the splitting of the Bragg reflection into two distinct Bragg wavelengths, which strongly differ regarding their refractive index sensitivities. Where one wavelength is only slightly affected by the ambient refractive index, the second Bragg peak shows a strong sensitivity. Furthermore, we investigate the temperature behaviour of the functionalized sensor and discuss it with respect to applications in refractive index sensin
Keywords: Bragg grating; high index layer; integrated waveguide; polymer optics; refractive index sensing